Integration and Innovation in Learning: A Comprehensive Study of Grade 10, 11, and 12 Students in Banten province - Dede Irman Pirdaus; Grida Saktian Laksito; Yasir Salih (International Journal of Ethno-Sciences and Education Research, 2024)
This research aims to evaluate curriculum transformation and integration of innovation in education in Banten province in the face of modern progress. Through a questionnaire to 50 high school students in grades 10 to 12, frequency distribution, class trends and the correlation between perceptions of innovation and skill improvement will be analyzed. The results show students' positive views towards the integration of innovation in all classes. A positive correlation was found between perceived innovation and skills improvement. Analysis of class trends revealed consistency of positive views across classes. Overall, the results of the analysis support students' acceptance of the integration of innovation in the curriculum and its impact on skill improvement.